Combined vitamin A and E therapy prevents retinal electrophysiological deterioration in abetalipoproteinaemia. Issue 12 (December 1982) - Bishara, S; Merin, S; Cooper, M; Azizi, E; Delpre, G; Deckelbaum, R J
Abstract : Eight patients with abetalipoproteinaemia had the typical ocular, systemic, and laboratory findings of this disease. Combined therapy with vitamins A and E was administered, starting as early as the first day of life and as late as 26 years of age. The patients were followed up for 2-6 years. Electroretinography was undertaken in all cases and electrooculography in some. After initiation of vitamin A and E therapy no progression of disturbed visual function could be detected in any patient. These objective tests of retinal function demonstrated that the combined vitamin A and E therapy may be useful in arresting retinal deterioration in abetalipoproteinaemia.